Settlement of exercise intensity using lactate curve as an indicator in summer training of cross-country skiers - Iwatsuki, T.; Suzuki, T.; Mizuochi, F.; Kondo, K. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: In the training of cross-country skiing, the adequate control of the exercise intensities in the base training with equal to or lower than lactate threshold (LT), speed training equal to or lower than onset of bold lactate accumulation (OBLA), and maximum training equal to or higher than OBLA are important themes with regard to enhancing the training effect. In cross-country skiing, roller ski or pole walk is implemented as a part of the summer training. The purpose of this study was to clarify the relationship between exercise styles and lactate curve by performing each lactate curve test in the roller ski and the pole walk.